Joint single-cell DNA accessibility and protein epitope profiling reveals environmental regulation of epigenomic heterogeneity - Chen, Xingqi; Litzenburger, Ulrike M.; Wei, Yuning; Schep, Alicia N.; LaGory, Edward L.; Choudhry, Hani; Giaccia, Amato J.; Greenleaf, William J.; Chang, Howard Y. (Nature communications, 2018)
Here we introduce Protein-indexed Assay of Transposase Accessible Chromatin with sequencing (Pi-ATAC) that combines single-cell chromatin and proteomic profiling. In conjunction with DNA transposition, the levels of multiple cell surface or intracellular protein epitopes are recorded by index flow cytometry and positions in arrayed microwells, and then subject to molecular barcoding for subsequent pooled analysis. Pi-ATAC simultaneously identifies the epigenomic and proteomic heterogeneity in individual cells. Pi-ATAC reveals a casual link between transcription factor abundance and DNA motif access, and deconvolute cell types and states in the tumor microenvironment in vivo. We identify a dominant role for hypoxia, marked by HIF1α protein, in the tumor microvenvironment for shaping the regulome in a subset of epithelial tumor cells. Cellular heterogeneity in cancer is complex and difficult to study. Here, the authors introduce Protein-indexed Assay of Transposase Accessible Chromatin (Pi-ATAC), which combines single cell chromatin and proteomic profiling to provide deep insight into the tumor microenvironment, and reveal the role of hypoxia in shaping the regulome of a subset of breast cancer cells in vivo.